Determinants of skilled attendance for delivery in Northwest Ethiopia: a community based nested case control study - Mengesha Zelalem Birhanu; Biks Gashaw Andargie; Ayele Tadesse Awoke; Tessema Gizachew Assefa; Koye Digsu Negesse (BMC, 2013)
Abstract Background The fifth Millennium Development Goal calls for a reduction of maternal mortality ratio by 75% between 1990 and 2015. A key indicator to measure this goal is the proportion of births attended by skilled health personnel. The maternal mortality ratio of Ethiopia is 676 deaths per 100,000 live births. Skilled birth attendance is correlated with lower maternal mortality rates globally and in Sub-Saharan Africa. However, the proportion of births with a skilled attendant is only 10% in Ethiopia. Therefore identifying the determinants of skilled attendance for delivery is a priority area to give policy recommendations. Methods A community based nested case control study was conducted from October 2009 - August 2011 at the University of Gondar health and demographic surveillance systems site located at Dabat district, Northwest Ethiopia. Data were obtained from the infant mortality prospective follow up study conducted to identify the determinants of infant survival. A pretested and structured questionnaire via interview was used to collect data on the different variables. Logistic regression analysis was used to identify the determinants of skilled birth attendance. Strength of the association was assessed using odds ratio with 95% CI. Results A total of 1065 mothers (213 cases and 852 controls) were included in the analysis. Among the cases, 166 (77.9%) were from urban areas. More than half (54%) of the cases have secondary and above level of education. Secondary and above level of education [AOR (95%CI) = 2.8 (1.29, 3.68)] and urban residence [AOR (95%CI) = 8.8 (5.32, 14.46)] were associated with skilled attendance for delivery. Similarly, women who had ANC during their pregnancy four or more times [AOR (95%CI) = 2.8 (1.56, 4.98)] and who own TV [AOR (95%CI) = 2.5 (1.32, 4.76)] were more likely to deliver with the assistance of a skilled attendant. Conclusions Women's education, place of residence, frequency of antenatal care visit and ever use of family planning were found to be determinants of skilled birth attendance. Encouraging women to complete at least secondary education and to have antenatal care frequently are important to increase skilled attendance during delivery.